Estudo da caracterização de ferramentas de corte texturizadas a laser e revestidas utilizadas no fresamento frontal de ferro fundido vermicular - Viana, Rhander (2009)
The controlled alteration of a surface can improve the performance of a mechanical part. The texture is the digital impression of a surface composed of hills and cavities, normally disordered distributed. When this texture is uniform and regularly distributed on a surface, it can modify significantly the functionality of a component. A technique used to uniformly modify a surface is the laser texture. The laser beam raises the temperature and promotes microstructural surface changes locally that can be beneficial to the component quality. The laser technique is relatively new, very versatile and it can be employed in several applications. In the present work a laser beam is used to clean and texture cutting tool s surfaces. The aim is to test this new technology after laser texturing cemented carbide inserts of the ISO grade K coated with TiAlN-Futura®, AlCrN-Alcrona® and AlCrN-Hélica®. The performance of these laser textured tools were confronted with the microblasted tools which is the commercial technique ordinarily used. Tool life test in face milling of compacted graphite cast iron - CGI (grade 450) were carried and the adhesivity of the coated layers on the substrates of the tools were characterized by Rockwell indentation, scratch tests with progressive load and wear test (calowear). In addition to that the topographies of the laser and microblating textures were investigated by 3D perfilometry device. The tool life results showed that the laser texture tool outperformed the microblating commercial tools under the cutting conditions tested. The adhesivity test results showed larger delamination on the microblasted tools than the laser textured tools. In the calowear tests the AlCrN-Hélica® presented the smallest wear coefficient followed by the TiAlN-Futura® and AlCrN-Alcrona® and on average the coefficients of the laser textured tools were lower than the microblasted tools. The topography obtained by 3D perfilometry showed that the substrate of the microblasting textured tools is more isotropic than the substrate of the laser textured tools.